Acute Ischemic Stroke and COVID-19: Experience From a Comprehensive Stroke Center in Midwest US - Grewal, Parneet; Pinna, Pranusha; Hall, Julianne P.; Dafer, Rima M.; Tavarez, Tachira; Pellack, Danielle R.; Garg, Rajeev; Osteraas, Nicholas D.; Vargas, Alejandro; John, Sayona; Da Silva, Ivan; Conners, James J. (Frontiers in Neurology, 2020)
Background: COVID-19 has been associated with increased risk of venous and arterial thromboembolism including ischemic stroke. We report on patients with acute ischemic stroke and concomitant COVID-19 in a diverse patient population. Methods: This is a retrospective analysis of patients hospitalized with acute ischemic stroke (AIS) and COVID-19 to our comprehensive stroke center in Chicago, IL, between March 1, 2020, and April 30, 2020. We reviewed stroke characteristics, etiologies, and composite outcomes. We then compared our cohort with historic patients with AIS without COVID-19 admitted in the same time frame in 2019 and 2020. Results: Out of 13 patients with AIS and COVID-19, Latinos and African-Americans compromised the majority of our cohort (76.8%), with age ranging from 31-80 years. Most strokes were cortical (84.6%) and more than 50% of patients had no identifiable source, and were categorized as embolic stroke of unknown source (ESUS). A trend towards less alteplase administration was noted in the COVID-19 stroke patients compared to the non-COVID group from 2020 and 2019 (7.1% vs 20.7% p 0.435 and 7.1% vs 27.2% p 0.178). Endovascular thrombectomy was performed in 3 (23%) patients. Systemic thrombotic complications occurred in 3 (23%) COVID-19 AIS patients. Median National Institutes of Health Stroke Scale and modified Rankin Scale at discharge were 11 (IQR 4-23) and 4 (IQR 3-4) respectively. In the logistic regression model corrected for age and sex, COVID-19 was associated with discharge to mRS>2 (p 0.046, OR 3.82, CI 1.02-14.3). Eight patients (63.8%) were discharged home or to acute rehabilitation, and two deceased from COVID-19 complications. Conclusion: AIS in the setting of COVID-19 is associated with worse outcomes, especially among African-American and Latino populations. Large vessel disease with ESUS was common suggesting an increased risk of coagulopathy and endothelial dysfunction as a potential etiology.